2018
DOI: 10.2478/agri-2018-0012
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Micronutrients (Fe And Zn) and Beneficial Nano-Scaled Elements (Si And Ti) on Some Morphophysiological Characteristics of Oilseed Rape Hybrids

Abstract: Current experiment was conducted to investigate the effects of foliar application of different nutrients (control, nano-chelated Fe, nano-chelated Zn, nano-TiO2, nano-Si) on seed yield and morpho-physiological characteristics of oilseed rape cultivars (Hydromel, Neptune, Nathalie, Danube, Alonso). The highest pod numbers was achieved by foliar application of Zn and nano-SiO2 in cv. Hydromel and Neptune. The heaviest seeds were recorded for plants treated with nano-SiO2. The highest seed yield was recorded for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
2
2
0
Order By: Relevance
“…Also, it seems that the application of FYM by improvement of soil conditions, facilitation of root growth, increasing the nutrients uptake, had prepared a uniform canopy as a suitable base for better absorption of bio-stimulants and micronutrients. The results are consistent with the results of some previous works (Pasandi et al, 2018;Kheyrkhah et al, 2018).…”
Section: Discussionsupporting
confidence: 93%
“…Also, it seems that the application of FYM by improvement of soil conditions, facilitation of root growth, increasing the nutrients uptake, had prepared a uniform canopy as a suitable base for better absorption of bio-stimulants and micronutrients. The results are consistent with the results of some previous works (Pasandi et al, 2018;Kheyrkhah et al, 2018).…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, it appears that the application of FYM improved soil conditions, promoted root growth, increased nutrient uptake, and provided a uniform canopy as a suitable platform for greater absorption of bio-stimulants and micronutrients, has improved soil conditions. The results are similar to certain earlier findings (Ahmad et al, 2012;Ali et al, 2010ab;Naveed et al, 2012;Pasandi et al, 2018;Kheyrkhah et al, 2018). To improve plant growth and development and boost chickpea production, it is required to apply farmyard and poultry manure.…”
Section: Path Coefficient Analysissupporting
confidence: 90%
“…The observed increase of Chl levels has been described in response to TiO 2 NPs, often paralleled with an increase of N uptake, but the targets of these NPs in the plant metabolism remain unknown (Lyu et al 2017). Kheyrkhah et al (2018) showed that SiO 2 and TiO 2 increased the chlorophylls and carotenoids content in oilseed rape cultivars. Also, Aliabadi et al (2015) showed that 100 mg/L TiO 2 NPs increased the Chl a content and the ratio (Chl a / Chl b) in T. aestivum.…”
Section: Discussionmentioning
confidence: 97%